Análise comparativa de módulos de resiliência obtidos com o Geogauge para o controle de qualidade de camadas granulares dos pavimentos - Maia, Camila Lima (2016)
In the mechanistic-empirical dimensioning methods of asphalt pavements, one of the main input parameters for the granular layers is the Resilience Module (MR), being important the development and diffusion of methods and equipment that aim to measure this property in the field. Geogauge is an equipment that seeks to determine the resilience modules of the pavement layers in situ, however, the modules obtained through it, differ from those determined in the triaxial test of repeated loads (TCR), due to several factors, such as: the difference On loading, the degree of compaction, humidity, etc. Thus, the present dissertation proposes to determine resilience modules of granular layers of pavements in situ, with Geogauge equipment, that allow to obtain correlations between the modules determined in the field and those obtained in the laboratory with the TCR test. For this, the materials of the different layers of the pavement, coming from road sections running in the state of Ceará, were tested both in the field, with the Geogauge, and in the laboratory, with the TCR test. The road segments used in this research refer to a 600-meter section of a highway and an experimental stretch of the Federal University of Ceará. In both, in situ tests, such as the sand vial tests, determinations of the humidity, and tests with the Geogauge equipment were carried out. In addition, samples were collected to perform laboratory tests, being: granulometry, LL, LP, compaction, CBR and MR assays. From the data obtained in the field and in the laboratory, a statistical analysis of regression was performed, being possible to determine a significant regression model to correlate the determined MRs with Geogauge and with the TCR, for a specific state of tension and granular material. It was also verified that the tests carried out with Geogauge present a good repeatability and reproducibility in general, being able to detect constructive problems, presenting potential to be used in the technological control of granular layers of flexible pavements.